Assessment Practices among College Instructors: Implications for Advancing Professional Development in Assessment Strategy Trainings - Ontok-Balah, K. (Researchparks Publishing, 2023)
A total of 24 faculty members from the main campus of the University of Southern Mindanao, Kabacan, Cotabato, Philippines voluntarily participated in a study evaluating the assessment practices utilized by college instructors and identifying their professional development needs in this area. Half of the participants held the entry-level academic position of Instructor in State Universities and Colleges (SUCs), and the majority of participants were women between the ages of 31 and 40. The participants also predominantly taught courses in the fields of social sciences. Data was collected through a survey focusing on classroom assessment practices. The findings revealed that the college instructors primarily utilized performance assessment for diagnostic purposes, to encourage students' learning, and as a tool to measure their performance in class. The commonly employed assessment practices included portfolio assessment, graded recitation, true or false tests, term papers or projects, assignments, multiple choice, class participation, and essays. Notably, a significant majority of participants consistently assigned activities that required students to articulate ideas and concepts, as well as engage in reviewing and retaining information taught in class. However, the study highlighted a limited integration of examinations emphasizing higher-order thinking skills, suggesting room for improvement. They recognized the significance of acquiring skills in creating precise and quantifiable learning outcomes. They also expressed concerns about the development of objective tests and the utilization of comprehensive observational checklists. Additionally, there was a clear emphasis on improving their understanding of test-scoring procedures and other assessment tools, signaling a critical area of focus for their professional growth.